First-principles investigation for the hydrogen storage properties of XTiH3 (X=K, Rb, Cs) perovskite type hydrides - Xu, Nanlin; Chen, Yan; Chen, Shanjun; Li, Song; Zhang, Weibin (International journal of hydrogen energy, 2024)
The perovskite-type hydride compounds are potential candidate materials in the field of hydrogen storage. This paper presents a systematical study of XTiH3 (X = K, Rb, Cs) using density functional theory. The analysis of formation energy, elastic properties and phonon dispersion curves indicate that all the studied materials are thermodynamically, mechanically and dynamically stable. By analyzing the B/G ratio, it is determined that these compounds are brittle materials. The electronic properties reveal that the XTiH3 compounds exhibit semi-metallic characteristics. The charge transfer characteristics of these compounds were analyzed using Bader partial charges. Moreover, the thermodynamic characteristics of these compounds were investigated and the dependence of their free energy, entropy and heat capacity on the temperature were analyzed. Finally, the gravimetric hydrogen storage capacities of KTiH3, RbTiH3 and CsTiH3 were calculated to be 3.36, 2.22 and 1.65 wt%, respectively. The hydrogen desorption temperatures of KTiH3, RbTiH3 and CsTiH3 were found to be 209 K, 161 K and 107 K, respectively. To our knowledge, this study represents the very first investigation of XTiH3 compounds and offers valuable references to this hydrogen storage material. [Display omitted] •XTiH3 (X = K, Rb, Cs) perovskite have been investigated using first-principles.•XTiH3 perovskite exhibit thermodynamic, mechanical and dynamical stability.•The gravimetric hydrogen storage capacity is found to be 3.36 wt% for KTiH3.